CARACTÉRISATION HYDROCHIMIQUE SAISONNIÈRE (ÉTIAGE ET CRUE) ET VULNÉRABILITÉ ENVIRONNEMENTALE DE LA RESSOURCE EN EAU DE LA RETENUE DE MOKOLO (EXTRÊME-NORD CAMEROUN) - Sara, Lewa; Auguste, Ombolo; Benguellah Benoit, Loura (European Scientific Journal, ESJ, 2014)
The contribution of this work is a hydrochemical characterization andstudy of the environmental vulnerability of the water resources of the waterretention of Mokolo in the Far North of Cameroon, built in 1979 bydamming the upstream part of the Mayo-Tsanaga, and which is used tosupply drinking water for a population of about 800,000 inhabitants. Extremeanthropogenic pressures during the period of low water make vulnerableresource towards the pollution while the wet season rainfall result insignificant changes in the mineralization of the water due to leaching fromagricultural land in the watershed. The analysis of the results shows avariation during low water and flood water of the hydrochemical faciesconsidering a diverse origin of acquisition of the mineralization factors. Inaddition, high concentrations of certain ions during flood highlight the extentof human agricultural activities on physicochemical quality of waterresources.